The Cys‐Pro motifs in the intrinsically disordered regions of the transcription factor BACH1 mediate distinct and overlapping functions upon heme binding. Issue 12 (27th March 2022) - Segawa, Kei; Igarashi, Kazuhiko; Murayama, Kazutaka
Abstract : The function of the transcription factor BACH1 is regulated by heme binding to multiple Cys‐Pro (CP) motifs within its intrinsically disordered regions. Here, biochemical analyses were conducted to reveal the individual functional roles of the CP motifs. Our findings revealed that four CP motifs in BACH1 individually contributed to the regulation of BACH1 activity by accepting heme in a five‐ and six‐coordination manner. The model structure around the bZip domain indicated that the CP motifs are in the N‐ and C‐terminal heme‐binding regions, which are approximately 9 nm apart, suggesting that spatial location is important for the individual function of the CP motifs. The presence of multiple CP motifs with distinct roles may ensure the multifaceted, strict regulation of BACH1 by heme. Abstract : The individual roles of the Cys‐Pro (CP) motifs, which are involved in heme binding, in the transcription factor BACH1 are unclear. These functional CP motifs are located within intrinsically disordered regions in BACH1. Each CP motif indicates an individual heme coordination type. Heme binding to CP motifs induces individual conformational changes that lead to multifaceted functional regulation of BACH1.